Suaeda australis and its associated rhizosphere microbiota: a comparison of the nutrient removal potential between different shrimp farm sediments in New Caledonia - Colette, Marie; Guentas, Linda; Della Patrona, Luc; Ansquer, Dominique; Callac, Nolwenn (Frontiers in Microbiology, 2023)
Shrimp rearing generate organic waste that is trapped in the pond sediment. In excess, these wastes may impair aquaculture ecosystem and shrimps' health. To promote the biological oxidation of accumulated organic waste, the pond is drained and dried at the end of each production cycle. However, this practice is not always conducive to maintaining microbial decomposition activities in sediments. Shrimp production in New Caledonia is no exception to this problem of pollution of pond bottoms. One promising way of treating this waste would be phytoremediation, using a native halophyte plant and its microbiota. Thus, this study explored the nutrient removal potential of Suaeda australis and its microbiota on sediments from four shrimp farms. Suaeda australis was grown in an experimental greenhouse for 6 months. In order to mimic the drying out of the sediments, pots containing only sediments were left to dry in the open air without halophytes. An analysis of the chemical composition and active microbiota was carried out initially and after 6 months in the sediments of the halophyte cultures and in the dry sediments for each farm respectively. In the initial state, the chemical parameters and the microbial diversity of the sediment varied considerably from one farm to another. Growing Suaeda australis reduced the nitrogen, phosphorus and sulphur content in all type of sediment. However, this reduction varied significantly from one sediment to another. The rhizosphere of Suaeda australis is mainly composed of micro-organisms belonging to the Alphaproteobacteria class. However, the families recruited from this class vary depending on the farm in question. Depending on the sediment, the variation in microbiota leads to different putative biochemical functions. For two of the farms, a similar reduction in nitrogen concentration was observed in both dry and cultivated sediments. This suggests that certain initial chemical characteristics of the sediments influence the nutrient removal efficiency of Suaeda australis. Our study therefore highlights the need to control the 2 This is a provisional file, not the final typeset article pH of sediments before cultivation or in dry sediments in order to ensure optimal microbial decomposition of organic waste and nutrient cycling.